2022
DOI: 10.1186/s12916-022-02354-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of circulating NMR metabolic biomarkers for type 2 diabetes risk in the UK Biobank study

Abstract: Background Effective targeted prevention of type 2 diabetes (T2D) depends on accurate prediction of disease risk. We assessed the role of metabolomic profiling in improving T2D risk prediction beyond conventional risk factors. Methods Nuclear magnetic resonance (NMR) metabolomic profiling was undertaken on baseline plasma samples in 65,684 UK Biobank participants without diabetes and not taking lipid-lowering medication. Among a subset of 50,519 pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 46 publications
6
37
0
Order By: Relevance
“…The present study provides, for the first time, detailed characterisation of the relevance of lipoprotein size and subclass particle concentrations to T2D risk in a Chinese population. As shown in previous Western population studies 5 , 25 , we observed higher T2D risk among participants with higher concentrations of large VLDL particles and lower concentrations of large HDL particles, smaller mean HDL particle size and large mean VLDL particle size, as well as higher TG levels and lower HDL-cholesterol levels. This is consistent with an insulin resistant state 26 , which is a well-established component of the causal relationship between adiposity and T2D 27 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present study provides, for the first time, detailed characterisation of the relevance of lipoprotein size and subclass particle concentrations to T2D risk in a Chinese population. As shown in previous Western population studies 5 , 25 , we observed higher T2D risk among participants with higher concentrations of large VLDL particles and lower concentrations of large HDL particles, smaller mean HDL particle size and large mean VLDL particle size, as well as higher TG levels and lower HDL-cholesterol levels. This is consistent with an insulin resistant state 26 , which is a well-established component of the causal relationship between adiposity and T2D 27 .…”
Section: Discussionsupporting
confidence: 88%
“…Recent prospective analyses among ~ 65,000 UK Biobank (UKB) participants examined the associations of 139 of the biomarkers considered herein (measured using the same NMR-metabolomics platform) with incident T2D (n = 1719) recorded during almost 12 years’ follow-up, adjusting for sociodemographic factors, fasting time, smoking, alcohol drinking and general and central adiposity 25 . Overall, the associations of 98 biomarkers were qualitatively consistent in the two study populations, including significant positive associations of 53 biomarkers with T2D risk and inverse associations of 27 biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…These data greatly extend the blood biomarker coverage in the UK Biobank and provide a wide span of molecular biomarkers not commonly measured in clinical practice, including amino acids, ketones and fatty acids. With over 118,000 plasma samples profiled in the UK Biobank, the addressable research questions extend vastly beyond biomarker discovery and the large sample size benefits, for example, causal analyses and risk prediction 9 , 13 , 14 , 17 . Due to the streamlined data access policy in UK Biobank, the data release opens possibilities for the research community to use the entire epidemiological toolbox to study the NMR biomarkers in relation to public health.…”
Section: Discussionmentioning
confidence: 99%
“…In this study of objectively measured concentrations of liver fat, detailed biomarker profiling showed multiple adverse characteristics with circulating lipids and metabolites. The patterns of these associations were associated with alterations in biomarkers linked to excess general adiposity [3, 4, 14–16], diabetes [17, 18], CVD [5, 6, 19, 20], and other major chronic diseases. Hazardous metabolic profiles linked to higher concentrations of fat in the liver involved higher levels of VLDL triglycerides, extremely large and very large lipoprotein concentrations, small HDL particles, glycolysis and inflammatory markers, MUFAs and SFAs, and amino acids.…”
Section: Discussionmentioning
confidence: 99%